Formation of wear-resistant TiN and (Ti1-x, Alx)N coatings using Dc Fil-Tered vacuum arc plasma; 7th International Conference on Modification of Materials with Particle Beams and Plasma Flows (Tomsk, Russia, 25-30 July 2004) - Ryabchikov A. I. Aleksandr Ilyich; Koval N. N. Nikolay Nikolaevich; Stepanov I. B. Igor Borisovich; Goncharenko I. M.; Sivin D. O. Denis Olegovich; Ryabchikov I. A.; Shulepov I. A. Ivan Anisimovich (2004, 2004)
The paper presents the results of investigation of structure, element composition andphysico-mechanical properties of TiN and (TiAl)N coatings deposited under combined treatment of surface by vacuum arc discharge and gaseous microparticle-free metal plasma flows. Also, perspectives of industrial application of combined technologies are discussed